AB1125-HPR Health- Related Quality of Life in Patients with Chronic Inflammatory Arthropathies and Biologic Therapy. (15th July 2016) - Άlvarez-Payero, M.; Maceiras, F.; Melero, R.; Mouriño, C.; Martin, A.; Rodríguez-Rodríguez, M.; Ucha, M.; Martínez, N.; Hernandez, I.; Barbazán, C.; Rodríguez, M.; Balboa, V.; et al.
Abstract : Background: Chronic inflammatory arthropaties-CIA (RA-rheumatoid arthritis, PA-psoriatic arthritis, and AS-ankylosing spondylitis) cause functional disability and reduces health-related quality of life (HRQoL) of patients 1 Objectives: To evaluate HRQoL in patients with CIA and biologic therapy (BT), as a measure of patient reported outcome. Methods: Descriptive cross-sectional study (August 2014) in a tertiary hospital. Inclusion criteria:a)adult patients with RA, PA, SA and other CIA (O) attended at the Rheumatology Service and b)≥2 months of treatment with BT (sc/iv adalimumab-ADA, sc/iv etanercept-ETA, iv infliximab, sc golimumab, sc certolizumab, sc/iv abatacept, sc/iv tocilizumab or iv rituximab). Sociodemographic and clinical variables were obtained by structured interview and review of medical record.Degree of disease activity measures: DAS28 index (≤3.2:low activity; >3.2-≤5.1:moderate; >5.1:high) for RA and PA peripheral; BASDAI (<4:low activity ≥4:high activity) for AS and PA with predominant axial involvement. HRQoL was mesured by a self-administered questionnaire:EQ5D-5L 2 . It evaluates 5 dimensions:mobility (M), self-care, usual activities (UA)pain/discomfort (PD) and anxiety/depression. Each dimension has 5 levels of severity. A HRQoL score is obtained (EQ-index) from 0 (death) to 1 (full health). It also has a visual scale (EQ-VAS) of global health from 0 (the worst health) to 100 (the best health). Descriptive and multiple linear regression analysis (LRA) were performed to determine which variables contributed on HRQoL. Results: A total of 382 patients were eligible for the study.314 patients agreed to answer the questionnaire (women:55.7%, average age (±SD): 55.2±13.9 years, average disease duration (±SD):13.05±8.1 years). Pathologies distribution: 44.3% RA, PA 26.1%, 21.3% AS, 8.3% O. BT: 51.9% ADA, 28.7% ETA and 19.4% others. 65.9% of patients had a first line of TB. 50% of patients had concomitant drug (corticosteroid/methotrexate/leflunomide). 71.7% of patients had low activity, with standard drug regimen (61.8%) and optimized regimen (37.6%). The EQ-index perceived was:0.73±0.22 and a global health EQ-VAS: 64.2±21.0 points. The worst rated questionnaire dimensions (severities 3–4-5) were P (33.7%), UA (29.9%) and M (26.7%). LRA showed significance differences (p<0.001) for disease activity, disease duration and education. 0.4 and 9.05 EQ-VAS points were reduced for each year of evolution and each DAS28 point increase, respectively. Differences were not significant for age, sex, pathology, drug or line number. Conclusions: Generally, patients evaluated have a good control of disease activity and an acceptable HRQoL perceived. Chronic P and loss of autonomy to perform UA are the worst rated dimensions References: Gerhold K, Richter A, Schneider M, Bergerhausen HJ, Demary W, Liebhaber A, et al. Heailth-related quality of life in patients with long-standing rheumatoid arthritis in the era of biologics: data from the German biologics register RABBIT. Rheumatology.2015; 54:1858–66. Rabin R, de Charro F. EQ-5D:a measure of health status from the EuroQol Group. Annals of Medicine. 2001; 33:337–43 Disclosure of Interest: M. Άlvarez-Payero: None declared, F. Maceiras: None declared, R. Melero: None declared, C. Mouriño: None declared, A. Martin: None declared, M. Rodríguez-Rodríguez: None declared, M. Ucha: None declared, N. Martínez: None declared, I. Hernandez: None declared, C. Barbazán: None declared, M. Rodríguez: None declared, V. Balboa: None declared, J. Uña: None declared, G. Piñeiro Grant/research support from: Pfizer, J. Pego Grant/research support from: Pfizer